Dr. Lieven Claessens (ICRISAT) on how to assess climate change adaptation options for farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Lieven Claessens of ICRISAT shares insights from work to assess different climate change adaptation strategies that could enhance the resilience and livelihoods of smallholder farmers in East Africa. More info at https://ccafs.cgiar.org/blog/how-do-you-assess-climate-change-adaptation-options-farmers-lessons-agmip Research presented at the Global Science Conference on Climate Smart Agriculture, University of California, Davis. 20-22 March 2013.